Epidemiological Studies on Infectious Bursal Disease in Broiler Chickens in Haryana, India - Mor, Sunil K.; Narang, G.; Jindal, N.; Mahajan, N.K.; Sharma, P.C.; Rakha, N.K. (International Journal of Poultry Science, 2010)
The epidemiological data of Infectious Bursal Disease (IBD) in 483 broiler chicken flocks were analyzed from July, 2005 to June, 2008. Overall morbidity, cumulative mortality and case fatality rate due to the disease were recorded as 4.54, 2.34 and 51.69%, respectively. Of the total IBD-affected flocks, 192, 211, and 80 flocks were affected during the years 2005-06, 2006-07 and 2007-08, respectively. Dullness, depression, anorexia, ruffled feathers and inability to move were evident in almost all the IBD-affected flocks. The affected birds had yellowish white or greenish yellow diarrhoea. At necropsy, the gross lesions were observed mainly in bursa of Fabricius followed by changes in thigh and breast muscles. The disease was recorded throughout the year. Maximum cases (52.80%) were observed in birds of 21-30 days of age followed by 33.13% in the age group of 31-40 days. Although the disease was observed in both IBD-vaccinated (334) and unvaccinated (149) flocks, percent morbidity and cumulative mortality were higher in unvaccinated flocks than in the vaccinated flocks. Factors like improper vaccination, poor biosecurity measures and existence of very virulent strains of IBD virus could be the reasons for disease in the vaccinated flocks. Continuous surveillance may help in better understanding of the epidemiology of infectious bursal disease virus in broiler chickens in this region.